Heaping and leaping: survey response behaviour and the dynamics of self-reported consumption expenditure - Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Survey respondents often use simple strategies to answer retrospective questions about their level of consumption expenditure, resulting in the heaping of data at certain round numbers. In the panel context, wave-to-wave leaping from one heap to another can distort the sample pattern of consumption movements over time. Using BHPS energy expenditure data, we show that respondents use a variety of different response strategies, often switching between those strategies. We estimate a joint model of the dynamics of consumption and response behaviour and find that neglect of response behaviour can lead to serious biases in empirical studies of consumption dynamics.
Keywords: 330